The Effect Of Dosage Of Mangrove Leaf Extract Avicennia Marina On The Viability Of Hela Cells - Mahbubur Rahman (Stem Cell Research and Development Center, Universitas Airlangga, 2021)
Cervical cancer is caused by infection with the Human Papilloma Virus (HPV) which attacks the reproductive organs of sexually active women. Treatment is done alternatively using natural materials such as mangrove plants. Avicennia marina is a type of mangrove plant that has been used in alternative medicine because of its potential as an anticancer. This study aimed to determine the effect of Avicennia marina mangrove leaf extract on the viability of HeLa cells. Avicennia marina mangrove leaf powder was extracted using graded maceration. The solvents used include n-hexane, ethyl acetate, and ethanol. The results showed that the LC50 value was 98.55 ppm, it means that the ethanol extract has toxic properties. Phytochemical test results of Avicennia marina mangrove leaf extract contain saponins, steroids/triterpenoids, flavonoids and tannins. The test results showed that the extract yield was 14.40%, the water content of the extract was 16.57%, and the total phenol was 1915.92 mg/g GAE. The results of the LC- MS test resulted in suspected compounds including Caffeine and Diosmetin. The ethanol extract of Avicennia marina mangrove leaves was cytotoxic to heLa cell viability with the resulting IC50 value of 115.345 g/mL.